SEJARAH DAMPAK KAJIAN MADRASAH TERHADAP TRANSFORMASI INTELEKTUAL ISLAM MASA KLASIK - Asep Kurniawan (IAIN Syekh Nurjati Cirebon, 2017)
The establishment of Madrasah as an educational institution is not purely educational. There is a political and ideological motif behind the stand. This motivation has implications for the study of madrasah which is thick with the content of religious science of Sunni version especially fiqih. The knowledge is more likely to recycle and preserve the establishment of religious doctrines, and less encourage creative critical thinking as in the natural sciences. Considerable impact is the development of intellectual transformation and subsequent Islamic civilization that stagnated with the closing of the door of ijtihad and the dichotomism of Islamic scholars. A historical problem that leads to the decline of Islam.